Impulsive Buying Behavior with Technology Acceptance Model and Promotions in E-Commerce Among Gen-Z Indonesians - Chandra, Eugene; Pradipta, Oktavian Rizki; Gilisen, Steven Gabriel; V. Layman, Chrisanty (Jurnal Studi Manajemen dan Bisnis, 2025)
Nowadays, Impulsive Buying Behavior (IBB) has become a trend among online shopping e-commerce users, where most of the users are Indonesian Gen-Zs’. Most of those behavior comes from due to many promotions, its usefulness, and its ease of using online shopping e-commerce. Its massive development of digital technology through online shopping e-commerce has changed consumer behavior, particularly among Generation Z’s, who represent the largest proportion of internet users in Indonesia. This demographic is highly engaged in online shopping and demonstrates strong tendencies toward impulsive buying. To investigate this phenomenon, this study explains the relationship of Technology Acceptance Model (TAM), with its promotional variables, to measure the determinants of Impulsive Buying Behavior (IBB) between Indonesian Gen Z online shopping e-commerce users. A quantitative explanatory research approach was employed, with data gathered via an online survey involving 200 participants from the Greater Jakarta region. The collected data were then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that Perceived Usefulness has a significant impact on impulsive buying behavior, whereas Perceived Ease of Use, Perceived Enjoyment, Sales Promotion, and Price Promotion do not exhibit a meaningful influence. This suggests that Gen Z consumers prioritize the functional value and effectiveness of e-commerce platforms over promotional deals or entertainment aspects.